2022
DOI: 10.3390/nu14050916
|View full text |Cite
|
Sign up to set email alerts
|

Tapioca Resistant Maltodextrin as a Carbohydrate Source of Oral Nutrition Supplement (ONS) on Metabolic Indicators: A Clinical Trial

Abstract: Tapioca resistant maltodextrin (TRM) is a novel non-viscous soluble resistant starch that can be utilized in oral nutrition supplements (ONS). This study aims to evaluate acute and long-term metabolic responses and the safe use of ONS containing TRM. This study comprised of two phases: In Phase I, a randomized-cross over control study involving 17 healthy adults was conducted to evaluate three ONS formulations: original (tapioca maltodextrin), TRM15 (15% TRM replacement), and TRM30 (30% TRM replacement). Plasm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 43 publications
(57 reference statements)
0
5
0
Order By: Relevance
“…As for the effect of soluble dietary fiber, the ONS with 23% of carbohydrates replaced with tapioca-derived resistant maltodextrin showed about 5% lower peak value of postprandial blood glucose than the standard ONS, but the difference was not significant [30]. On the other hand, the ONS with 8% of total carbohydrates replaced with soluble dietary fiber (polydextrose) and 15% with a low glycemic response-carbohydrate (fructose) reported a 33% reduction in postprandial blood glucose iAUC compared to the control ONS [31].…”
Section: Discussionmentioning
confidence: 93%
“…As for the effect of soluble dietary fiber, the ONS with 23% of carbohydrates replaced with tapioca-derived resistant maltodextrin showed about 5% lower peak value of postprandial blood glucose than the standard ONS, but the difference was not significant [30]. On the other hand, the ONS with 8% of total carbohydrates replaced with soluble dietary fiber (polydextrose) and 15% with a low glycemic response-carbohydrate (fructose) reported a 33% reduction in postprandial blood glucose iAUC compared to the control ONS [31].…”
Section: Discussionmentioning
confidence: 93%
“…90 % of ERMs reach the large intestine and 50 % are fermented ( 41 ), they have been shown to function as prebiotics and can increase the production of short-chain fatty acids ( 30 ). In addition, there are reports that justify their use for satiety ( 42 ), mass control ( 13 ) and control of blood sugar levels ( 40 ). All this allows us to theorize that the ERM from makal obtained in this study could be associated with positive metabolic profiles when used as a functional food ingredient.…”
Section: Resultsmentioning
confidence: 99%
“…Based on the abundant evidence in scientific literature on beneficial health effects of ERM such as indigestibility ( 12 ), fermentability and mass control ( 13 ), the present research aims to synthesize ERM from a non-conventional plant source of starch, makal ( Xanthosoma yucatenense ), by applying a factorial design based on response surface methodology. First, a pyrodextrinization process was developed (using three variables: m (starch)/ V (acid) ratio, temperature and reaction time), followed by a complementary hydrolysis (using two variables: α-amylase per pyrodextrin volume fraction and reaction time) to finally synthesize ERM.…”
Section: Introductionmentioning
confidence: 99%
“…The last one, based on 12 studies, showed limited evidence with no effect of RS2 on the glycemic profile and control of these patients [ 34 ]. Recently, studies have shown that RS4 reduced fasting glycemia and HbA1c in prediabetic subjects [ 35 ] and significantly lowered level in fasting plasma insulin and HOMA-IR (Homeostasis Model Assessment of Insulin Resistance) indicating a better insulin sensitivity following the ingestion of RS, even if HbA1c and fasting blood glucose did not change [ 36 ]. As in healthy subjects, RS stimulates the production of SCFAs by the microbiota, modulating the production of incretins, with beneficial effects on insulin production and sensitivity, and glucose disposal in tissues [ 31 ▪▪ ].…”
Section: Effects Of Slowly Digestible Starch and Resistant Starch On ...mentioning
confidence: 99%